Analysis of the Correlation between Combustion Products in Biomass Thermal Power Plant Using Association Rule Mining - Saša Igić; Dragana Bošković; Barbara Vujkov; Nemanja Igić; Todor Janić; Dalibor Jeličić; Vladica Ristić; Boris Dumnić (Energies, 2020)
The biomass combustion process is inevitably accompanied by the emission of pollutant gasses. This paper gives a comprehensive analysis of the external variables and combustion products of the biomass plant. The analyzed data were collected from 18 MWt boiler in combined heat and power plant Sremska Mitrovica over a period of four months. The correlations between the recorded data were determined using a unique methodology, which is based on association rule mining. The results of the study can be further used for the reduction of the harmful combustion products, as well as for the optimization of the operation process.